Analisis Profesionalitas Aparatur Sipil Negara Berdasarkan Pengukuran Indeks Profesionalitas ASN (IP ASN) di Badan Perencanaan Pembangunan dan Penelitian Pengembangan Daerah Provinsi Kepulauan Bangka Belitung - Yunindyo Sasmito (Nakhoda: Jurnal Ilmu Pemerintahan, 2022)
This study analyzes the level of professionalism of the State Civil Apparatus (SCA) in the Regional Development Planning and Research Agency (BAPPEDA) of the Bangka Belitung Islands Province. The method used in this study refers to the calculation of the Professionalism Index of the State Civil Apparatus (IP ASN). The data is sourced from the IP ASN Questionnaire for all civil apparatus in the BAPPEDA environment, totaling 74 people. The results of this study indicate that the professionalism of BAPPEDA ASN is in the medium category with an average BAPPEDA ASN IP score of 72.90. Of the four existing dimensions, BAPPEDA excels in the discipline dimension with no civil apparatus receiving disciplinary punishment, the majority of the performance dimensions get a good predicate, and the qualification dimension with educational levels that have met the job requirements. Then the competency dimension saw that 1 (one) structural official had not carried out leadership training and 7 functional officials had not carried out functional training, 57 percent had attended technical training, and 72 percent had attended seminars/workshops. Increased competence development is needed in order to increase the professionalism of employees.